Referrals for new client acquisition in professional services. Issue 1 (9th January 2017) - Grierson, Stuart; Brennan, Ross
Abstract : Purpose: The purpose of this paper is to address the following research question: What are the perceptions of professionals and consumers regarding the antecedents of client referrals in the financial advice sector? Design/methodology/approach: A total of 61 qualitative interviews were conducted, with the following three key groups: independent financial advisers (IFAs; 20 interviews), clients of IFAs (26 interviews) and consumers who manage their own financial affairs and do not use the services of an IFA (15 interviews). Findings: The financial advisers interviewed believe that client referrals are important to their business success, that they can influence clients to become ambassadors who will consciously seek out new clients and that excellent service will motivate clients to provide referrals. However, the interviews with the clients painted a different picture. While advisers believe that they can influence client referral behavior, the clients did not believe that they were influenced by the adviser to make referrals. Research limitations/implications: The sampling method was non-random and relied on the professional contacts of the principal researcher as a starting point, from which a network of contacts was established to identify interviewees. The study casts doubt on the ability of professional service providers to influence client referral behavior. This novel finding deserves further research investigation. Practical implications: There is clearly scope for greater measurement in connection with referrals in professional service businesses. The propensity for clients to refer should be included as a metric in the performance measurement of professional service providers, in addition to standard financial measures. This would encourage the service provider to consider referrals during client interactions. Originality/value: The study reports on a substantial qualitative study involving both professional service providers and their clients. While the providers believe that client referrals are critical to their business success, the evidence collected provides little or no support for this belief. Clients report they are not motivated to refer. Advisers do not explicitly measure referrals. The reality of referrals seems not to match the mythology.